Cell subpopulations in failed human corneal grafts - Kuffová, L; Holán, V; Lumsden, L; Forrester, J V; Filipec, M (The British journal of ophthalmology, 1999)
BACKGROUND/AIMS: Inflammatory cells and antigen presenting cells (APC) are not present under normal circumstances in the centre of the healthy cornea. The purpose of this study was to investigate and phenotype the inflammatory cell populations, particularly with reference to T cell subpopulations and macrophages, and to localise dendritic cells (DC) and other MHC class II positive cells in three groups of grafted corneas: rejected non-inflamed, rejected inflamed grafts, and control dystrophic explants. METHODS: 15 corneal buttons removed during keratoplasty from non-inflamed "quiet" previously grafted corneas, five inflamed corneas requiring urgent regrafting for "graft melting" (in "high risk" corneas), and 10 control dystrophic opaque corneas explanted during their first graft procedure were examined. Cryosections of corneas were immunostained with a panel of monoclonal antibodies (mAb) against CD3, CD4, CD8, CD14, CD25, CD68, HLA-DP, and HLA-DR molecules using the StreptABC method. DC were detected by dual immunostaining as CD1a+ and MHC class II+ and CD19-. Cell densities in immunostained tissue sections were evaluated using a scale from 0 to +4. RESULTS: Immunostaining in control dystrophic corneas was negative for all antibodies. A moderate to high density of CD8+, CD14+, and CD68+ cells was observed in the majority of rejected non-inflamed as well as in rejected inflamed corneal buttons. Strong positivity for HLA-DP and HLA-DR molecules in the epithelium, stroma, and endothelium was also demonstrated. Weak positivity for CD4 and CD25 was observed in six of 15 and 11 of 15 rejected corneas, respectively. The presence of dendritic cells in the basal layer of the epithelium and in the stroma was observed in 50% of the grafts. CONCLUSIONS: A high frequency of macrophages, the presence of DC in the explants, and strong expression of HLA-DP and HLA-DR molecules on resident cells are characteristics of rejected corneal allografts, whether actively inflamed or not. The presence of DC in the stroma of the grafted cornea suggests that they may be mainly responsible for T cell activation and graft rejection since DC are known to be a 100-fold more potent than macrophages as APC.
Keywords: fluorescenční protilátková technika; Humans; lidé středního věku; Corneal Transplantation; dendritické buňky; Immunoenzyme Techniques; Graft Rejection; Female; Aged; makrofágy; dospělí; imunofenotypizace; senioři; lidé; transplantace rohovky; HLA-DR antigeny; T-lymfocyty - podskupiny; T-Lymphocyte Subsets; Adult; imunoenzymatické techniky; Immunophenotyping; HLA-DR Antigens; HLA-DP Antigens; ženské pohlaví; Male; Middle Aged; Dendritic Cells; Adolescent; Fluorescent Antibody Technique; Macrophages; mužské pohlaví; HLA-DP antigeny; rejekce štěpu; mladiství